Strategic customer relationship management: laying the ground for CRM implementation in SME contex - Pinho, Vânia Maria da Silva (2019)
In the current competitive market scenario, the need for companies to stand out from each other is ever growing. Therefore, strategic management is increasing their focus on customer relationships as a competitive advantage, understanding that nowadays customers look for much more than just a product or service, but rather a full personalised experience that meets (or hopefully exceeds) both their needs and expectations. Customer Relationship Management (CRM) comes up as the best solution to organisations that decide to adopt these relationship marketing focused strategies. Unlike big multinationals, the high investment in technological systems and complexity of internal procedures always kept Small and Medium Enterprises (SME) in a more traditional circuit regarding CRM. However, the competition increase, market globalisation, technological development and frailty of customer preferences have led many SME to rethink their business strategy and include CRM as one of the main competitive advantages when dealing with customers. Which leads to the research question raised by this Project: how to lay the ground for CRM implementation in SME context? – More specifically applied to the small company KontaGion Hub, Ltd. Following this question, the aim of the current Project is to propose a specific CRM implementation strategy tailored to the needs of the observed case company. To achieve this, the present investigation followed the method of unique case study in a British start-up, and as data sources there were made interviews, secondary documents were analysed, and a series of activities and physical observations were made during the Project length, for a period of approximately 6 months. The main contribution of this Project is the proposal of a CRM implementation strategy adapted to the SME company KontaGion Hub specific needs. Considering this type of companies hold a significant weight in any business market across Europe, and due the lack of further investigations carried out in this field, this work can represent a step further in the implementation of strategic CRM projects in other SME context.